Risk-Based Evaluation of Sanitation Hygiene at Drinking Water Refill Depot of PT Y, Surabaya: Evaluasi sanitasi higiene Berbasis Risiko di Depo Air Minum PT. Y Surabaya - Muhammad Ibnu Fauzi; Aussie Amalia (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The drinking water depot at PT. Y is crucial for employees to support their work and prevent dehydration and fatigue. However, if health standards are not optimally implemented, it can increase the possibility of contamination, which can impact water quality and employee health. Good drinking water is water that is free from physical, chemical, and microbiological contamination. This study aims to ensure that sanitation and hygiene standards at PT. Y are in good condition. This depot uses raw water from the mountains, transported by tanker trucks and treated through a silica filtration system, activated carbon, micron membranes, and ultraviolet light disinfection. The study used an observation and evaluation approach. Data collection was carried out through observation and interviews. The hygiene and sanitation assessment refers to the Risk-Based Food Hygiene and Sanitation Guidelines issued by the Ministry of Health in 2021. After conducting the analysis, the results showed that the drinking water depot at PT. Y generally complies with most sanitation and hygiene requirements, both for quality standard equipment and for handlers. This is evidenced by a very high inspection score of 96.4, indicating a low risk of non-conformity. However, there were minor deficiencies in the building and raw water aspects, for which there were no purchase receipts. These deficiencies can be used as evaluation points for improvements during future audits.